Peran Pembelajaran IPS Berbasis Kewirausahaan dalam Membangun Karakter Mandiri Siswa SD Kelas 5 - Adinda Putri Ramadhani; Rohmah Annisa; Oman Farhurohman (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
This study aims to explore the role of entrepreneurship-based social studies learning in building the independent character of 5th grade elementary school students. Using a qualitative approach, this study examines the impact of implementing entrepreneurial learning in the context of social studies on the development of students' independent attitudes, social skills, and ability to innovate. Data were obtained through literature review and content analysis of various relevant literatures, as well as observation of entrepreneurship learning practices in elementary schools. The results show that entrepreneurship-based social studies learning significantly contributes to improving students' independent character, including the ability to make decisions, manage resources, and innovate in solving problems. In addition, this learning also strengthens students' social skills, such as cooperation, communication and leadership. This research suggests that entrepreneurship-based social studies learning should be further expanded at the primary school level to support better development of students' independent character and prepare them to face future social and economic challenges.